The Effect of local injection of strontium on inhibition and repair of orthodontically induced root resorption in rats (An experimental study) (Mustansiria Dental Journal, 2018)
Background: Strontium (Sr) is an alkaline earth trace metal cation that has a highaffinity for hydroxyapatite. This study aimed to examine the histological effect oflocally injected strontium (Sr) on prevention and repair of induced root resorptionof rat molar subjected to orthodontic tooth movement.Materials and Methods: Eighteen ten-week- old male Wister rats were randomlydivided into two groups of nine animals for two experiments. In both experiments;uniform standardized expansive springs were used to move maxillary first molarsbuccally for three weeks and then removed. In experiment No.1, at the time ofspring placement, 0.25 ml of the strontium chloride solution at a concentration 240mg/ml was injected at the sub-periosteum of the buccal side of the maxillary leftfirst molar which was the experimental side. On other hand, 0.25 ml of distilledwater was injected at the sub-periosteum of the buccal side of the right maxillaryfirst molar which was the control side. The injections repeated every other day forthree weeks whereas in experiment 2 it was begun at the day of spring removal andrepeated every other day for another three weeks. After that the animals werescarified humanly and biopsies were taken for histological examination.Results: In experiment 1 the side injected with strontium showed statisticallysignificant lesser root resorption than control side, while in experiment two thestrontium injected side showed significantly more repair.Conclusion: Results of the study suggested that local injection of strontium caninhibit root resorption process and enhance repair.